The Justice Dilemma in Minor Marriages: Dispensation vs. Prevention - Suthida Chaturathorn; Setyaning Wida Nurul Anggaretno; Harith Badrul; Jaxon Woods; Ariana Oliveira (Unnes Law Journal, 2025)
In Indonesia, the issue of minor marriages has long been a contentious subject, intersecting with complex legal, cultural, and ethical dimensions. The legal framework governing marriage, particularly the stipulations outlined in the Marriage Law No. 1 of 1974, sets the minimum marriage age at 16 for women and 19 for men, but exceptions have often been made under certain circumstances. The practice of granting dispensations for underage marriages through religious and civil courts, particularly in rural areas, raises significant concerns regarding child protection and gender equality. This paper explores the legal paradox of minor marriages in Indonesia, focusing on the tension between granting dispensations (legal exceptions) and the broader need for prevention policies to protect children’s rights and ensure gender justice. Through an analysis of judicial practices, statutory regulations, and the socio-cultural context, the study examines how the legal system both enables and limits efforts to combat child marriage. It critiques the role of judicial discretion in granting dispensations to minor marriages and highlights the challenges faced by policymakers in harmonizing national law with international human rights standards, such as the Convention on the Rights of the Child (CRC). The paper argues that while legal dispensation offers a temporary solution, it inadvertently perpetuates systemic inequalities, particularly for young girls. The study calls for a reexamination of the legal framework to prioritize prevention, reinforce protections for children, and align Indonesia’s marriage laws with international standards of justice and child welfare.